(untitled) (Revista Puertorriqueña de Psicologia, 2020)
This writing provides a book review about atheists and agnostics in Puerto Rico to visible and knows the beliefs and experiences of 29 prominent people in psychology in Puerto Rico. Even in the year 2020, a feeling of mistrust permeates atheists and agnostics in the American continent. It has been estimated that between 450 to 500 million people worldwide identify themselves as agnostic or atheistic. Studies conducted with non-believers in the United States found that approximately 41% of atheists have experienced some form of discrimination during their lives. This book offers an opportunity to make visible experiences and educate the Puerto Rican public about the agnostic and atheistic community by demystifying a variety of misconceptions that continue to exist. In the text, 25 participants who self-identify as agnostics or atheists present personal narratives that explore and share their experiences by responding to a series of questions about their personal and professional lives regarding their lack of spiritual and/or religious beliefs.